Capoeira, corpo, espiritualidade : as percepções de corpo, ethos e visão de mundo de crianças, de dez a doze anos, praticantes de capoeira em uma Escola Municipal de Porto Alegre : um estudo de caso - Siega, Carson Luiz (2007)
This dissertation is the study related to Capoeira, Body and Spirituality, based on 10-12 years-old children's perception of their body and own world, during an one-year-period. The subject was developed having the support of Capoeira expertise authors, as well as Anthropology, Theology and Human Development scholars' literature, under the Children's Psychology scope, aiming the building of a case study. The study is an investigation which took place in a Porto Alegre Public School EMEF José Loureiro da Silva, involving fifteen (15) students who are involved in a Capoeira project Projeto Capoeira Da Escola. This paper is composed by three chapters. In Chapter 1, one will make some considerations on the origin, spread and development of this Art/Martial Fight, and one will also present the concept of a 'Capoeira Master' (Mestre de Capoeira) and how the concept was created. One will also show the relationship between Capoeira and the Brazilian Old Republic political scenario in the 1930's, and how Capoeira has become a Brazilian cultural symbol and a national identity. In Chapter 2, one will present four topics related to ones research: the Body, based on an Anthropological point of view; the Spirituality; Capoeiristas (people who practice Capoeira) view of world and children's development, focusing the age of this study group of children involved in the research, and a summary of the study. In Chapter 3, one will present an interpretation of the research data and the methodological option adopted by the researcher, which was the qualitative method, thus one will explain one's assumptions about the subject. One went through field research and data collection based on the children's study group, who has practiced Capoeira for a minimum of one year period, and on one's personal experience as a Capoeira teacher since 1983. According to a questionnaire with open and closed answers, one will make an analysis and a comments about the collected data. The research brought the conclusion about very interesting perceptions based on people's answers to the questionnaire about Capoeira. Those perceptions might contribute for a further study on the topic and, a deeper study on the topic might bring us new possibilities of the use of Capoeira as a means in education.